Efektivitas Antibakteri Ekstrak Rimpang Jahe Merah (Zingiber officinale var rubrum) Terhadap Pertumbuhan Bakteri Staphylococcus aureus Secara In Vitro - Erny Tandanu (Universitas Prima Indonesia, 2020)
Background: Staphylococcus aureus is a bacteria that often infects humans. Currently more than 95% of S.aureus are resistant to penicillin and widespread bacterial resistance to antibacterials available today, prompting the importance of more effective antibacterials. One of the natural substances that can be used as an antimicrobial is red ginger (zingiber officinale var rubrum). Red ginger contains some antibacterial compounds such as essential oils, flavonoids, terpenoids, phenols, and zingberene. Objective: To determine the antibacterial effect of red ginger rhizome extract in inhibiting the growth of Staphylococcus aureus bacteria. Methods: This research uses True Experimental laboratory design with maseration method. The subjects of the study were red ginger rhizome ethanol extract (The extract tested antimicrobial activity against Staphylococcus aureus by using the Disk Diffusion method. with concentration series 25% w / v, 50% w / v, 75% w / v, 100% w / v and positive control using ciprofloxacin and negative control using DMSO. Placement of 4 repetitions for each concentration and control tested on bacteria. Results: The results showed that red ginger extract had antibacterial activity, where the average inhibition zone diameter formed at concentrations of 25%, 50%, 75%, and 100% was in the order of 10.21 mm, 11.27 mm, 11.75 mm, and 13.17 mm. The drag zone diameter increases as the concentration increases. And the mean of positive control zone inhibition zone is 21.75 mm and negative control no inhibition zone is formed. Conclusion: Present study verifies the antibacterial effect of red ginger extract in inhibiting the growth of Staphylococcus aureus bacteria.